Composite coating and application thereof

By using block copolymers of polyethersulfone and polyoxazoline as the bottom layer of the composite coating, the problem of poor compatibility of polyethersulfone and polytetrafluoroethylene is solved, the adhesion and durability of the coating are improved, the risks of yellowing and shedding are reduced, and better cookware performance is achieved.

CN119912847AActive Publication Date: 2025-05-02WANHUA CHEM GRP CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510410609.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-05-02
Estimated Expiration
2045-04-02

AI Technical Summary

Technical Problem

The existing Teflon non-stick pot coatings have poor compatibility between polyether sulfone and polytetrafluoroethylene, which leads to complex manufacturing process and easy peeling during use, which affects the service life and appearance. At the same time, the hydrophobicity of polyether sulfone requires the addition of organic solvents to increase production costs and environmental pollution.

Method used

Block copolymer is used as the bottom layer of the composite coating, and the block copolymer consists of a polyethersulfone segment and a polyoxazoline segment. The block copolymer is prepared by a ring-opening polymerization reaction of a polyethersulfone containing a -CH2X group on the terminal benzene ring and an oxazoline monomer.

Benefits of technology

It improves the adhesion between the coating and the metal substrate, reduces the risk of coating falling off, reduces the yellowness index, improves the yellowing resistance and non-stick properties of the coating, and improves the durability and aesthetics of the cookware.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to a non-stick pan coating, in particular to a composite coating and application thereof, the composite coating comprises a surface layer and a bottom layer, the surface layer comprises polytetrafluoroethylene, the bottom layer comprises a block copolymer, and the block copolymer comprises a polyethersulfone chain segment and a polyoxazoline chain segment. The composite coating provided by the embodiment of the invention has good metal adhesion, and can improve the durability of cookware when being used for non-stick cookware.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite coating, in particular to a composite coating and application thereof. Background Art

[0002] The coating of Teflon non-stick pans is usually composed of three layers: an outer layer of polytetrafluoroethylene (PTFE), a middle layer of polyamide-imide (PAI), and an inner layer of polyethersulfone (PES). Polyethersulfone is known for its excellent heat resistance and strong adhesion to metal substrates, which enables it to be closely bonded to the base material of the pan, providing long-lasting durability and ensuring that the coating is not easy to peel off. However, due to the poor compatibility between polyethersulfone and polytetrafluoroethylene, an intermediate layer of PAI is required to achieve an effective combination of the two. This multi-layer structure increases the complexity of the manufacturing process and may cause peeling and discoloration of the coating during daily use, which in turn affects the service life and appearance of the pan.

[0003] In addition, due to its hydrophobicity, polyethersulfone, when used as the main component of coatings, often needs to add organic solvents as diluents, which not only increases production costs, but also causes environmental pollution. In order to enhance the compatibility of polyethersulfone with polytetrafluoroethylene, polyethersulfone needs to be processed into ultrafine powder, which not only increases costs, but also makes the production process more complicated. Summary of the invention

[0004] To overcome at least one defect of the above-mentioned prior art, in a first aspect, the present invention provides a composite coating, comprising a surface layer and a bottom layer, wherein the surface layer comprises polytetrafluoroethylene, and the bottom layer comprises a block copolymer, wherein the block copolymer comprises a polyethersulfone segment and a polyoxazoline segment.

[0005] In one embodiment, the weight average molecular weight of the polyethersulfone segment is 40,000 to 100,000 g / mol; and / or, In the block copolymer, the mass content of the polyoxazoline segment is 5 to 40%.

[0006] In one embodiment, the weight average molecular weight of the polyethersulfone segment is 50,000 to 95,000 g / mol; and / or, In the block copolymer, the mass content of the polyoxazoline segment is 15 to 40%.

[0007] In one embodiment, the polyoxazoline segment is a poly(2-ethyl-2-oxazoline) segment; and / or, In the block copolymer, the mass content of the polyoxazoline segment is 28-40%; and / or, The weight average molecular weight of the polyethersulfone segment is 80000 to 91000 g / mol; and / or, The polyethersulfone segment has the following structural units: .

[0008] In one embodiment, the method for preparing the block copolymer comprises the following steps: Prepare a polyethersulfone containing a -CH2X group on the terminal benzene ring, and then initiate a ring-opening polymerization reaction of an oxazoline monomer through the -CH2X group to obtain the block copolymer; Here, X is a halogen atom.

[0009] In one embodiment, the preparation process of the polyethersulfone containing a -CH2X group on the terminal benzene ring comprises: The reaction mixture is reacted at 140-200° C. for 2-6 hours, and then the reaction system is reacted at 160-230° C. for 2-48 hours, and then a capping agent is added to the system; wherein the reaction mixture comprises a first monomer, a second monomer and a salt-forming agent; and / or, The process of the ring-opening polymerization reaction comprises: The polyethersulfone and oxazoline monomers containing a -CH2X group on the terminal benzene ring are reacted at 90-110° C. to obtain the block copolymer.

[0010] In one embodiment, X is a chlorine atom or a bromine atom; and / or, The salt-forming agent includes one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate; and / or, The first monomer includes bisphenol S, and the second monomer includes one or more of dichlorodiphenyl sulfone and difluorodiphenyl sulfone; and / or, The end-capping agent includes one or more of 4-chlorobenzyl chloride, 4-chlorobenzyl bromide, 4-fluorobenzyl bromide, 4-fluorobenzyl chloride, 2-fluoro-4-bromobenzyl bromide, and 2-chloro-4-fluorobenzyl bromide.

[0011] In a second aspect, the present invention provides a cooking utensil comprising the above-mentioned composite coating.

[0012] In a third aspect, the present invention provides a block copolymer comprising a polyethersulfone segment and a polyoxazoline segment.

[0013] In a fourth aspect, the present invention provides the use of the above-mentioned block copolymer in the preparation of Teflon composite coatings or cookware.

[0014] The composite coating of the invention has good metal adhesion and can be used in non-stick cookware to improve the durability of the cookware. DETAILED DESCRIPTION

[0015] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.

[0016] One embodiment of the present invention provides a block copolymer including a polyethersulfone segment and a polyoxazoline segment.

[0017] In one embodiment, the block copolymer is polyethersulfone- b -Polyoxazoline diblock copolymer.

[0018] In one embodiment, the polyethersulfone segment comprises a sulfone group (-SO2-) and an arylene group.

[0019] In one embodiment, the polyethersulfone has the following structural units: .

[0020] In one embodiment, the weight average molecular weight of the polyethersulfone segment can be 40,000 to 100,000 g / mol, further can be 50,000 to 95,000 g / mol, and further can be 80,000 to 91,000 g / mol, for example, 60,000 g / mol, 70,000 g / mol, 75,000 g / mol, 85,000 g / mol, 88,000 g / mol, 89,000 g / mol, and 90,000 g / mol.

[0021] In one embodiment, in the block copolymer of polyethersulfone and polyoxazoline, the mass content of the polyoxazoline segment can be 5-40%, further can be 15-40%, further can be 28-40%, for example 6%, 10.5%, 11%, 12%, 15%, 18%, 19%, 20%, 25%, 28%, 29%, 30%, 35%, 39%. Wherein, the content or molecular weight of the polyoxazoline segment in the block copolymer can be adjusted by controlling the molar ratio of the oxazoline monomer to the polyethersulfone segment.

[0022] In one embodiment, the monomers for preparing the polyethersulfone chain segment include a first monomer and a second monomer, the first monomer includes bisphenol S, and the second monomer includes one or more of dichlorodiphenyl sulfone (e.g., 4,4'-dichlorodiphenyl sulfone) and difluorodiphenyl sulfone (e.g., 4,4'-difluorodiphenyl sulfone). Further, the polyethersulfone chain segment can be prepared by a nucleophilic substitution reaction of the monomers.

[0023] In one embodiment, the oxazoline monomer used to prepare the polyoxazoline segment includes 2-ethyl-2-oxazoline.

[0024] In one embodiment, the preparation process of the block copolymer of polyethersulfone and polyoxazoline includes: first preparing a polyethersulfone containing a -CH2X group on the terminal benzene ring, and then initiating a ring-opening polymerization reaction of the oxazoline monomer through the -CH2X group to prepare a block copolymer. The ring-opening polymerization reaction can be, for example, a cationic ring-opening polymerization.

[0025] In one embodiment, X in the -CH2X group (benzyl halide) on the terminal benzene ring of the polyethersulfone is a halogen atom, such as chlorine or bromine.

[0026] One embodiment of the present invention provides a method for preparing the above block copolymer, comprising the following steps: Prepare a polyethersulfone containing a -CH2X group on the terminal benzene ring to obtain a polyethersulfone containing an initiating group; The ring-opening polymerization of oxazoline monomers was initiated by polyethersulfone containing initiating groups to prepare polyethersulfone- b - polyoxazoline block copolymers; Here, X is a halogen atom (eg, a chlorine atom or a bromine atom).

[0027] In one embodiment, polyethersulfone is prepared by a nucleophilic substitution reaction, and a small molecule containing a specific group is used for end-capping to obtain a polyethersulfone containing an initiating group, and the cationic ring-opening polymerization of the oxazoline monomer is further initiated by the polyethersulfone to obtain a polyethersulfone- b -Polyoxazoline amphiphilic block copolymers.

[0028] In one embodiment, polyethersulfone can be prepared by reacting a first monomer and a second monomer. Further, the preparation process of polyethersulfone containing a -CH2X group on the terminal benzene ring (or polyethersulfone containing an initiating group) includes: The reaction mixture is reacted at 140-200° C. (first reaction temperature) for 2-6 hours, and then the reaction system is reacted at 160-230° C. (second reaction temperature) for 2-48 hours, and then a capping agent is added to the system; wherein the reaction mixture includes a first monomer, a second monomer and a salt-forming agent.

[0029] In one embodiment, the weight average molecular weight of the polyethersulfone containing the initiating group is the same as the molecular weight of the polyethersulfone segment, and the molecular weight distribution of the polyethersulfone may be 1.70 to 1.75, such as 1.71, 1.72, 1.73, and 1.74.

[0030] In one embodiment, the amount ratio of the first monomer to the second monomer can be 1:1.0 to 1:1.03; the amount of the salt-forming agent can be 1.05 to 1.3 times the amount of the first monomer, for example, 1.1 times, 1.15 times, 1.2 times, or 1.25 times.

[0031] In one embodiment, the reaction mixture for preparing the polyethersulfone containing an initiating group includes a first monomer, a second monomer, a salt-forming agent, and an organic solvent.

[0032] In one embodiment, the organic solvent used in the preparation of the polyethersulfone containing an initiating group includes a first organic solvent.

[0033] In one embodiment, the organic solvent used in the preparation process of the polyethersulfone containing an initiating group includes a first organic solvent and a second organic solvent, and the preparation process may include the following steps: Mixing the first monomer, the second monomer, the salt-forming agent, the first organic solvent, and the second organic solvent to obtain a reaction mixture; and The reaction mixture is refluxed at 140-200° C. for 2-6 hours, the second organic solvent is then evaporated, the reaction system is reacted at 160-230° C. for 2-48 hours, and then a capping agent is added to the system.

[0034] In one embodiment, the first monomer, the second monomer, and the salt-forming agent may be immersed in the first organic solvent in sequence, and then the second organic solvent is added to the system under stirring.

[0035] In one embodiment, the amount of the first organic solvent used is such that the solid content of the reaction system reaches 20-45wt% (e.g., 25wt%, 30wt%, 35wt%, 40wt%), and the amount of the second solvent used is 0-20wt% (e.g., 1wt%, 2wt%, 5wt%, 10wt%, 15wt%) of the first solvent.

[0036] In one embodiment, during the preparation of polyethersulfone or polyethersulfone containing an initiating group, the first reaction temperature can be, for example, 145°C, 150°C, 155°C, 160°C, 170°C, 180°C, 190°C, and the reaction time can be, for example, 3h, 4h, 5h.

[0037] In one embodiment, in the preparation process of polyethersulfone or polyethersulfone containing an initiating group, the second reaction temperature can be, for example, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, and the reaction time can be, for example, 3h, 3.5h, 4h, 5h, 6h, 8h, 10h, 12h, 15h, 20h, 25h, 30h, 35h, 40h, 45h.

[0038] In one embodiment, during the preparation of polyethersulfone or polyethersulfone containing an initiating group, after the reaction at the first reaction temperature is completed, the second organic solvent in the reaction system can be evaporated by increasing the system temperature.

[0039] In one embodiment, during the preparation of polyethersulfone or polyethersulfone containing an initiating group, after the reaction at the second reaction temperature is completed, a capping agent is added to the system, followed by post-treatment. The post-treatment may include: filtering, crushing, washing, and vacuum drying the reaction fluid.

[0040] In one embodiment, the first monomer may be bisphenol S, the second monomer may be one or more of dichlorodiphenyl sulfone (eg, 4,4'-dichlorodiphenyl sulfone) and difluorodiphenyl sulfone (eg, 4,4'-difluorodiphenyl sulfone), and the oxazoline monomer may be 2-ethyl-2-oxazoline.

[0041] In one embodiment, the salt-forming agent may include one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate. Further, the salt-forming agent may be potassium carbonate and / or sodium carbonate.

[0042] In one embodiment, the first organic solvent may include dimethyl sulfoxide, dimethyl sulfone, N , N -dimethylformamide, N , N -Dimethylacetamide, N -methyl pyrrolidone, sulfolane or one or more. Further, the first organic solvent may be N , N -Dimethylacetamide, N - one or more of methyl pyrrolidone and sulfolane.

[0043] In one embodiment, the second organic solvent may include one or more of toluene, xylene, o-xylene, and chlorobenzene.

[0044] In one embodiment, the capping agent may include one or more of 4-chlorobenzyl chloride, 4-chlorobenzyl bromide, 4-fluorobenzyl bromide, 4-fluorobenzyl chloride, 2-fluoro-4-bromobenzyl bromide, and 2-chloro-4-fluorobenzyl bromide.

[0045] In one embodiment, the process of the ring-opening polymerization of the oxazoline monomer comprises: reacting a polyethersulfone having a -CH2X group on the terminal benzene ring and an oxazoline monomer at 90-110° C. to obtain a block copolymer.

[0046] In one embodiment, the ring-opening polymerization reaction temperature of the oxazoline monomer can be 92°C, 95°C, 98°C, 100°C, 102°C, 105°C, 108°C; the time can be 0.5 to 6 hours, for example 0.5h, 1h, 2h, 3h, 4h, 5h, 6h.

[0047] In one embodiment, polyethersulfone containing an initiating group is mixed with oxazoline under a nitrogen atmosphere, the temperature is raised to 90-110° C., and the above system is reacted under magnetic stirring to obtain polyethersulfone- b -Polyoxazoline block copolymers.

[0048] In one embodiment, the preparation reaction of the polyethersulfone chain segment and / or the ring-opening polymerization reaction of the oxazoline monomer can be carried out in a nitrogen atmosphere, and the reaction container used can be baked, dried and dehydrated, and vacuumed and filled with nitrogen multiple times.

[0049] One embodiment of the present invention provides a composite coating (or Teflon composite coating), including a surface layer and a bottom layer, the surface layer comprises polytetrafluoroethylene, and the bottom layer comprises the above-mentioned block copolymer.

[0050] In one embodiment, the composite coating is disposed on the surface of the cookware through a primer layer.

[0051] In one embodiment, the method for preparing the block copolymer film (or layer) comprises the following steps: 15 to 35 parts by mass of polyethersulfone- b -polyoxazoline block copolymer, 35-55 parts by weight of water and 10-50 parts by weight of a third organic solvent are mixed to form a dispersion; the dispersion is dried at a temperature of 200-380° C. to form a film.

[0052] In one embodiment, the third organic solvent may be one or more of chloroform, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0053] In one embodiment, polyethersulfone- b The thickness of the -polyoxazoline block copolymer film can be 10 to 2000 μm, for example, 50 μm, 100 μm, 200 μm, 250 μm, 300 μm, 350 μm, 500 μm, 1000 μm, 1200 μm, 1500 μm, 1800 μm.

[0054] In one embodiment, polyethersulfone- b The yellowness index of the polyoxazoline block copolymer film is less than 10, and may further be 5 to 9, such as 5, 6, 7, 8, or 9.

[0055] One embodiment of the present invention provides a cooker, comprising the above-mentioned composite coating or the above-mentioned block copolymer of polyethersulfone and polyoxazoline (polyethersulfone- b -polyoxazoline block copolymer).

[0056] In one embodiment, the cookware is a utensil for cooking (such as a non-stick pan), and the composite coating is at least disposed on the inner surface of the cookware.

[0057] One embodiment of the present invention provides the use of the above-mentioned block copolymer of polyethersulfone and polyoxazoline (or the block copolymer membrane of polyethersulfone and polyoxazoline) in the preparation of Teflon composite coating.

[0058] The block copolymer of polyethersulfone and polyoxazoline in one embodiment of the present invention is an amphiphilic copolymer comprising a hydrophobic polyethersulfone segment and a hydrophilic polyoxazoline segment, which can be well dissolved in polar organic solvents or used to prepare water-based coatings and has good film-forming properties and biocompatibility.

[0059] The block copolymer of polyethersulfone and polyoxazoline according to one embodiment of the present invention has the characteristics of good compatibility with polytetrafluoroethylene, low yellowness index and excellent water dispersibility. The use of the block copolymer in Teflon coating can effectively improve the adhesion between the coating and the applied substrate (such as metal) and reduce the risk of coating shedding.

[0060] The block copolymer membrane of polyethersulfone and polyoxazoline according to one embodiment of the present invention has better metal adhesion and lower yellowness index than the polyethersulfone membrane.

[0061] The block copolymer membrane of polyethersulfone and polyoxazoline according to one embodiment of the present invention has better hydrophilicity and adhesion, and lower yellowness than the polyethersulfone membrane.

[0062] In the composite coating of one embodiment of the present invention, the presence of the polyoxazoline chain segment improves the yellowing resistance of the coating, so that the coating can still maintain its original color after long-term use.

[0063] The composite coating according to one embodiment of the present invention has good non-stick properties and metal adhesion and can be used as a non-stick coating for cookware.

[0064] The composite coating of one embodiment of the present invention has better metal adhesion and low yellowness coefficient, thereby improving the durability and aesthetics of the coating or cookware.

[0065] Hereinafter, the preparation and application of the block copolymer of polyethersulfone and polyoxazoline according to one embodiment of the present invention will be further described in conjunction with examples. The test methods involved in each example are as follows.

[0066] Test Method 1. Weight average molecular weight and molecular weight distribution (PDI) The molecular weight of polyethersulfone was determined by gel permeation chromatography (GPC), with dimethylformamide (DMF) containing 20 mmol lithium bromide as the mobile phase, polymethyl methacrylate (PMMA) as the standard sample, and the chromatographic columns were Agilent MIXD C, MIXDD, and MIXD E in series, with a flow rate of 1.0 mL / min.

[0067] 2. Adhesion test to metal Polyethersulfone- b -The dispersion of poly(2-ethyl-2-oxazoline) was sprayed on the cleaned metal surface to form a coating, and the adhesion strength between the coating and the metal substrate was measured according to the cross-cut test method of ASTM D3359.

[0068] 3. Yellowness test Yellowness index The yellowness index was measured according to the method specified in ASTM E313.

[0069] Example 1 Preparation of polyethersulfone containing initiating groups 51707g of sulfolane was added into a 100L reactor, and then 15016g of bisphenol S (60mol), 17230g of dichlorodiphenyl sulfone (60mol), and 9951g of potassium carbonate (72mol) were added into the sulfolane in sequence, and then 10341g of xylene was added into the reactor under stirring, and the mixture was heated to 160°C (first reaction temperature) and refluxed for 5h. When no water was produced, the temperature was increased to completely evaporate the xylene in the reactor, and then the mixture was reacted at 220°C (second reaction temperature) for 3h, and then 4-chlorobenzyl chloride was added for end-capping. Finally, the reaction liquid was filtered, crushed, washed with water, and vacuum dried to obtain polyethersulfone containing initiating groups.

[0070] Polyethersulfone- b - Preparation of poly(2-ethyl-2-oxazoline) block copolymers Under nitrogen atmosphere, 100 g of the polyethersulfone containing the initiating group prepared above was added to a reaction bottle, and then 24 mL of 2-ethyl-2-oxazoline monomer was added, and then the system was heated to 100° C. to initiate bulk polymerization of oxazoline; after reacting for 2 h, the polymerization was terminated with 5 mL of NaOH aqueous solution (0.2 mol / L), and vacuum dried to constant weight to obtain polyethersulfone- b -poly(2-ethyl-2-oxazoline) block copolymer (PES- b -PEOX).

[0071] The obtained polyethersulfone containing initiating groups was tested according to the above method, and its weight average molecular weight was measured to be 90580 g / mol, and the molecular weight distribution was 1.71; the polyethersulfone- b -The mass content of poly(2-ethyl-2-oxazoline) segments in poly(2-ethyl-2-oxazoline) is 19.3%.

[0072] Polyethersulfone- b -Preparation of poly(2-ethyl-2-oxazoline) membrane 25 parts by mass of the polyethersulfone prepared aboveb -Poly (2-ethyl-2-oxazoline) powder, 40 parts by mass of deionized water, and 35 parts by mass of N-methylpyrrolidone were mixed and stirred to form a uniform polyethersulfone- b -poly (2-ethyl-2-oxazoline) dispersion, the dispersion is dried at a high temperature of 350°C to form a film, and the thickness of the film is 300 μm.

[0073] According to the above method, polyethersulfone- b -poly(2-ethyl-2-oxazoline) dispersion was sprayed on the metal surface for adhesion test. The results showed that the adhesion between the film and the metal met the ASTM grade 5B requirements. b The yellowness test of the poly(2-ethyl-2-oxazoline) film showed a yellowness index of 6, indicating that the film had good color stability and low yellowness.

[0074] Heat polytetrafluoroethylene to a molten state, add the polyethersulfone- b -poly(2-ethyl-2-oxazoline) powder was stirred, and the polyethersulfone powder could adhere to the surface of polytetrafluoroethylene without stratification, indicating that polytetrafluoroethylene and polyethersulfone- b -Poly (2-ethyl-2-oxazoline) has better adhesion.

[0075] Example 2 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- b -poly(2-ethyl-2-oxazoline) and its membrane, the only difference is that: in the preparation of the polyethersulfone containing an initiating group, N-methylpyrrolidone is used instead of cyclopentane sulfone; the second reaction temperature is 200°C, the reaction time is 6h; the amount of 2-ethyl-2-oxazoline used is 12mL.

[0076] The obtained polyethersulfone containing initiating groups was tested according to the above method, and its weight average molecular weight was 90145 g / mol, and the molecular weight distribution was 1.70; the polyethersulfone- b -The mass content of poly(2-ethyl-2-oxazoline) segments in poly(2-ethyl-2-oxazoline) is 10.5%.

[0077] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion test of poly(2-ethyl-2-oxazoline) to metals shows that it meets the ASTM grade 5B requirements.

[0078] The same method as in Example 1 was used to prepare polyethersulfone- b - Yellowness test of poly(2-ethyl-2-oxazoline) film showed a yellowness index of 8, indicating that the film has good color stability and low yellowness.

[0079] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion Test of Poly(2-ethyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- b -Poly (2-ethyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.

[0080] Example 3 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- b -poly(2-ethyl-2-oxazoline) and its membrane, the only difference is that: in the preparation of the polyethersulfone containing the initiating group, toluene is used instead of xylene; the second reaction temperature is 230°C, the reaction time is 2h; the amount of 2-ethyl-2-oxazoline used is 40mL.

[0081] The obtained polyethersulfone containing initiating groups was tested according to the above method, and its weight average molecular weight was 90890 g / mol, and the molecular weight distribution was 1.74; the polyethersulfone- b -The mass content of poly(2-ethyl-2-oxazoline) segments in poly(2-ethyl-2-oxazoline) is 28.5%.

[0082] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion test of poly(2-ethyl-2-oxazoline) to metals shows that it meets the ASTM grade 5B requirements.

[0083] The same method as in Example 1 was used to prepare polyethersulfone- b - Yellowness test of poly(2-ethyl-2-oxazoline) film showed a yellowness index of 5, indicating that the film has good color stability and low yellowness.

[0084] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion Test of Poly(2-ethyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- b -Poly (2-ethyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.

[0085] Example 4 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- b -poly(2-ethyl-2-oxazoline) and its membrane, the only difference is that: in the preparation of the polyethersulfone containing the initiating group, sodium carbonate is used instead of potassium carbonate; the second reaction temperature is 210°C, the reaction time is 5h; the amount of 2-ethyl-2-oxazoline used is 65mL.

[0086] The obtained polyethersulfone containing initiating groups was tested according to the above method, and its weight average molecular weight was 89950 g / mol, and the molecular weight distribution was 1.74; the polyethersulfone- b -The mass content of poly(2-ethyl-2-oxazoline) segments in poly(2-ethyl-2-oxazoline) is 39.3%.

[0087] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion test of poly(2-ethyl-2-oxazoline) to metals shows that it meets the ASTM grade 5B requirements.

[0088] The same method as in Example 1 was used to prepare polyethersulfone- b - Yellowness test of poly(2-ethyl-2-oxazoline) film showed a yellowness index of 5, indicating that the film has good color stability and low yellowness.

[0089] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion Test of Poly(2-ethyl-2-oxazoline) to Polytetrafluoroethylene and Polyethersulfone- b -Poly (2-ethyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.

[0090] Example 5 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- b -poly (2-ethyl-2-oxazoline) and its membrane, the difference is that: in the preparation of polyether sulfone containing initiating groups, N,N -Dimethylacetamide replaces sulfolane, the second reaction temperature is 160°C, the reaction time is 48h; the amount of 2-ethyl-2-oxazoline used is 6mL.

[0091] The obtained polyethersulfone containing initiating groups was tested according to the above method, and its weight average molecular weight was 90240 g / mol, and the molecular weight distribution was 1.73; the polyethersulfone- b The mass content of poly(2-ethyl-2-oxazoline) segments in poly(2-ethyl-2-oxazoline) is 5.6%.

[0092] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion test of poly(2-ethyl-2-oxazoline) to metals shows that it meets the ASTM grade 5B requirements.

[0093] The same method as in Example 1 was used to prepare polyethersulfone- b - Yellowness test of poly(2-ethyl-2-oxazoline) film showed a yellowness index of 9, indicating that the film has good color stability and low yellowness.

[0094] The same method as in Example 1 was used to prepare polyethersulfone- b - Adhesion Test of Poly(2-ethyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- b -Poly (2-ethyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.

[0095] Comparative Example 1 Preparation of polyethersulfone This example uses substantially the same raw materials and process as Example 1 to prepare polyethersulfone.

[0096] Preparation of polyethersulfone membrane 25 parts by mass of the polyethersulfone powder prepared above, 40 parts by mass of water and 35 parts by mass of N-methylpyrrolidone were mixed and stirred to form a polyethersulfone dispersion, and the dispersion was dried at a high temperature of 350° C. to form a film with a thickness of 300 μm.

[0097] The polyethersulfone dispersion was subjected to an adhesion test according to the aforementioned method, and the results showed that it met the ASTM grade 3B requirements. The polyethersulfone was subjected to a yellowness test according to the aforementioned method, and the yellowness index was 20.

[0098] When polytetrafluoroethylene is heated to a molten state and polyethersulfone powder is added and stirred, the polyethersulfone powder cannot adhere to the surface of polytetrafluoroethylene and the two are separated into layers, indicating that the adhesion between polytetrafluoroethylene and polyethersulfone is poor.

[0099] Table 1 lists the differences and performance parameters of the polymer films of various embodiments and comparative example 1.

[0100] Table 1 Structural parameters and performance parameters of polymer films of various embodiments and comparative example 1

[0101] According to the result of Example 1 and Comparative Example 1 in Table 1, compared to Comparative Example 1, the embodiment of the present invention, by adopting the block copolymer of polyether sulfone and polyoxazoline as the bottom layer of composite coating, can make coating have better adhesion and low yellowness coefficient, improves the durability and aesthetics of coating. Further, the difference between Examples 1 to 5 is mainly that the content of polyoxazoline segment in the block copolymer is different. According to the result of Table 1, the yellowness index of Example 1,3,4 is lower than that of Example 2,5. Thus, in the block copolymer of polyether sulfone and polyoxazoline, the mass content of polyoxazoline segment is preferably 15~40%, more preferably 28~40%.

[0102] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0103] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.

Claims

1. A composite coating, characterized in that: The invention comprises a surface layer and a bottom layer, wherein the surface layer comprises polytetrafluoroethylene, and the bottom layer comprises a block copolymer, and the block copolymer comprises a polyethersulfone segment and a polyoxazoline segment.

2. The composite coating according to claim 1, characterized in that: The weight average molecular weight of the polyethersulfone segment is 40,000 to 100,000 g / mol; and / or, In the block copolymer, the mass content of the polyoxazoline segment is 5 to 40%.

3. The composite coating according to claim 1, characterized in that: The weight average molecular weight of the polyethersulfone segment is 50,000 to 95,000 g / mol; and / or, In the block copolymer, the mass content of the polyoxazoline segment is 15 to 40%.

4. The composite coating according to claim 1, characterized in that: The polyoxazoline segment is a poly(2-ethyl-2-oxazoline) segment; and / or, In the block copolymer, the mass content of the polyoxazoline segment is 28-40%; and / or, The weight average molecular weight of the polyethersulfone segment is 80000 to 91000 g / mol; and / or, The polyethersulfone segment has the following structural units: 。 5. The composite coating according to claim 4, characterized in that: The preparation method of the block copolymer comprises the following steps: Prepare a polyethersulfone containing a -CH2X group on the terminal benzene ring, and then initiate a ring-opening polymerization reaction of an oxazoline monomer through the -CH2X group to obtain the block copolymer; Here, X is a halogen atom.

6. The composite coating according to claim 5, characterized in that: The preparation process of the polyethersulfone containing a -CH2X group on the terminal benzene ring comprises: The reaction mixture is reacted at 140-200° C. for 2-6 hours, and then the reaction system is reacted at 160-230° C. for 2-48 hours, and then a capping agent is added to the system; wherein the reaction mixture comprises a first monomer, a second monomer and a salt-forming agent; and / or, The process of the ring-opening polymerization reaction comprises: The polyethersulfone and oxazoline monomers containing a -CH2X group on the terminal benzene ring are reacted at 90-110° C. to obtain the block copolymer.

7. The composite coating according to claim 6, characterized in that: X is a chlorine atom or a bromine atom; and / or, The salt-forming agent includes one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate; and / or, The first monomer includes bisphenol S, and the second monomer includes one or more of dichlorodiphenyl sulfone and difluorodiphenyl sulfone; and / or, The end-capping agent includes one or more of 4-chlorobenzyl chloride, 4-chlorobenzyl bromide, 4-fluorobenzyl bromide, 4-fluorobenzyl chloride, 2-fluoro-4-bromobenzyl bromide, and 2-chloro-4-fluorobenzyl bromide.

8. A cooking utensil, characterized in that: A composite coating comprising any one of claims 1 to 7.

9. A block copolymer, characterized in that It comprises a polyethersulfone segment and a polyoxazoline segment.

10. Use of the block copolymer according to claim 9 in preparing Teflon composite coatings or cooking utensils.

Citation Information

Patent Citations

  • Aromatic polyethersulfone block copolymers

    CN102803341A

  • Water-based polyether sulfone non-stick coating without containing pentadecafluorooctanoic acid

    CN107892747A

  • Double-layer coating composition with polyethersulfone / polyaniline prime coat and polyethersulfone / polytetrafluoroethylene top coat, and preparation method of double-layer coating

    CN111718650A

  • Polyoxazoline-polyester block copolymer and preparation method thereof

    CN116804084A

  • High-flux polyethersulfone block copolymer porous microfiltration membrane with hourglass structure as well as preparation method and application of high-flux polyethersulfone block copolymer porous microfiltration membrane

    CN118341281A